The Effect of Fraud Hexagon on Financial Statement Fraud in Companies in the Health Sector Listed on the Indonesia Stock Exchange (IDX) in 2020-2023 - Yuyung Nur Jayanti; Mukhzarudfa Mukhzarudfa; Salman Jumaili (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the effect of the Fraud Hexagon on Financial Statement Fraud in Companies in the Health Sector listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The sample in this study was a Health Company using the Purposive Sampling technique so that 19 companies were obtained with 4 years of observation (76 observation data) that met the criteria. The analysis method used in this study is the classical assumption test, multiple linear regression analysis, and hypothesis testing with the help of SPSS V30 For Windows software. Data collection methods are by documentation and literature study. The results of the study concluded that partially opportunity has an effect and pressure, rationalization, capability, arrogance and collusion do not affect financial statement fraud. Simultaneously pressure, opportunity, rationalization, capability, arrogance and collusion affect financial statement fraud.